Radni okvir integracije repozitorija objekata za učenje sa sustavima za upravljanje učenjem : doktorski rad - Jerković, Hrvoje (H. Jerković ; Fakultet elektrotehnike i računarstva, 2012)
Different Learning Management Systems have become standard form of delivery of materials for electronic learning. They also implement various educational activities in online environment. Modern Learning Management Systems implement various Web 2.0 technologies and offer teachers, course designers and administrators a full range of advanced features that significantly relieves users in administering courses, users, tools and learning materials. A key problem with the Learning Management Systems stems from the fact that they are designed from the earliest stages as a closed system in order to serve users in single institution. Therefore data sharing with other systems is not supported except on a local level (between different courses of individual Learning Management Systems). In recent years, in the field of Learning Management Systems, little has been done in terms of interoperability with other Web-based systems. Projects that are present in this area in most cases have never experienced the implementation in practice. Today we are witnessing that almost all systems of any relevance have successfully migrated into the web environment, and those who are already present in web environment work intensively on integration with other related web systems, allowing users to use various forms of reuse and exchange of data. Besides, users today don't want to be separated from other systems and services while they edit their materials for electronic learning, or while they work with various tools in the Learning Management Systems. Painstaking process of searching through a multitude of inappropriate materials, problems with the retrieval, editing and publication of electronic learning materials on the courses is something that is a common routine of every lecturer that uses the Learning Management System. The processes of sharing and reuse of electronic learning materials are not present in today's Learning Management Systems, or if they are present then they are not implemented in proper way. So when users create new content on Learning Management System they don't have service or application integrated into Learning Management System that could be used in a simple way for searching of existing information in order to create new content for learning. Also if a user wants to quickly update electronic learning materials present on one or more courses, she or he does not have a quick and effective way to do it. Very often it all boils down to download of particular document, editing on users computer, and then uploading of the same document back on the course on Learning Management System. During that process usually there is no documentation of what has been done. So processes for versioning, reusing, exchanging or online editing of electronic learning materials are not supported in today's Learning Management System. Also there is no easy way to publish content to one or more desired courses on Learning Management System. One of the main goals of the key institutions in the area of electronic learning is tracking of students’ efforts through various activities in courses on Learning Management Systems and sequencing and navigation of content and activities based on that information. Many electronic learning standards brought complex procedures that allows the construction of such functionalities but in practice the implementation of these features has not been realized or they've been really poorly utilized. A key reason for this is the fact that data model that is used to facilitate those functionalities is not adequate for storage that would allow other important options for searching, reusing and exchange of electronic learning materials. And without proper implementation of those core options functionalities of sequencing and navigation of content cannot be fully and properly utilized. So, as mentioned before, problem that arises from the core architecture of Learning Management Systems is the data model that is used for storage and other forms of data management. This data model is very poor, limited and prevents adequate search and reuse of learning materials in present Learning Management Systems. Therefore access by other systems or tools for sharing and dissemination of learning materials is almost completely disabled. So current Learning Management Systems don't allow the implementation of applications (web or desktop for example) which could easily access electronic learning content and tools in the Learning Management System. Since there is no clearly defined data model that could allow storage of digital object so querying, describing, tagging, editing and searching through electronic learning documents and its structure is not supported which also disables much needed interoperability with other applications and systems. The second chapter of this work explains basic concepts of electronic learning and the implementation of various forms of electronic learning. This chapter also describes classical systems that are commonly used in electronic learning and sets out their differences and specifics and also brings example of practical instructor-led electronic learning. The third chapter presents an analysis of standards that are essential today in electronic learning. This chapter describes a number of rules which are used for defining the structure of objects for electronic learning. Here is also explained how Learning Management Systems based on this standardized rules function. The aim of this chapter is to examine existing systems and standards with emphasis on the feasibility study of options that are proposed in this work. There is already a number of projects in the field of Learning Management Systems which tried to make some improvements in this field so entire fourth chapter is devoted to the study of those projects. Numerous projects have attempted to accomplish individual functions that are often not applicable to any Learning Management System. Although none of these projects has seen widespread use, however on the end of this chapter is described how pooling of the efforts of individual projects could bring substantial progress in this area. The fifth chapter brings analysis of the system that could adequately upgrade the existing Learning Management Systems; and those are repositories of digital objects. Therefore special attention was given to the architecture of digital repositories. This chapter also explains different procedures for storage and editing of digital objects. Repository application programming interfaces for building mechanisms for editing of digital objects stored in repository are carefully analyzed. The sixth chapter analyzes the protocols for the storage of digital objects in digital objects repositories. Chapter brings thorough analyses and testing of today's most used implementations of digital repositories and their application interfaces and protocols which could be used to implement the proposed integration. During testing, first prototype application was created which helped to reach an understanding of advantages and disadvantages of existing application interfaces and repository implementations. Seventh, the key chapter, brings proposal of complete integration of Learning Management Systems and repositories for learning objects based on previously analyzed standards, protocols and implementation of existing repositories. In this chapter, prototype application is made that implements a framework of integrated Learning Management System and digital objects repository. Chapter demonstrated the feasibility of the searching and processing of digital objects stored in multiple repositories. Prototype of framework also demonstrates functionalities that allow retrieval and processing of data from different Learning Management System. Among other functionalities proposed framework also demonstrates how to allow full control and integration of one electronic learning tool from Learning Management Systems with variety of repositories of digital objects. This proves the feasibility of the proposed Register of electronic tools. Chapter eight provides a summary of implemented features and also brings further explanation of Registry of electronic tools with guidelines for further development of an framework of integrated Learning Management System and digital objects repository. This doctoral work gives a review of the research areas of Learning Management Systems with an emphasis on systems that are now commonly in use. This work explores the area of digitalization of content, content processing and digital objects storage systems. Ways of structuring and processing of digital objects are also analyzes with emphasis on their applicability to serve as supporting procedures to Learning Management Systems. Special attention is given to modern repositories for the storage of digital objects and their possibility to integrate with Learning Management Systems. Therefore this work brings proposal for the quality integration of Learning Management Systems and digital object repositories. Work also describes proposed structure of digital objects data model for use in Learning Management System and proposes the process of creating own tools which could be implemented through proposed framework for integration of Learning Management Systems and digital object repositories. -